ENDOSCOPIC MONITORING OF PATIENTS WITH GASTROINTESTINAL TUMORS: MODERN APPROACHES AND PROSPECTS - Yusupov Oybek Maksud o‘g‘li (Web of Journals Publishing, 2025)
Malignant tumors of the gastrointestinal (GI) tract remain one of the leading causes of cancer morbidity and mortality worldwide. Late diagnosis persists as a major challenge, with over 60% of patients being identified at stages III–IV. Endoscopic monitoring utilizing advanced mucosal visualization technologies significantly improves early detection of neoplastic lesions and precancerous conditions. The use of HD-endoscopy, narrow-band imaging (NBI), endoscopic ultrasonography, capsule endoscopy, and artificial intelligence-assisted systems has demonstrated a 25–40% reduction in mortality according to international data. The article presents an overview of current endoscopic approaches and their impact on improving oncological outcomes.
Keywords: Endoscopy, early cancer, GI tract, screening, NBI, artificial intelligence.